Characterization of crosslinked nanocellulose from oil palm frond fibers for enhanced drug-loaded hydrogels in antibacterial application - Kong, Y. L.; Leong, M. Y.; Harun, M. Y.; Wong, W. F.; Looi, C. Y. (Elsevier, 2025)
This study investigates the antibacterial efficacy and material properties of gelatin-based hydrogels incorporated with nanocellulose derived from oil palm frond fibers (CNC) and crosslinked with glutaraldehyde (GA) to optimize drug delivery systems. The hydrogels were loaded with either erythromycin (ERY) or tetracycline hydrochloride (TAC) and evaluated against Pseudomonas aeruginosa. Results demonstrated that the inclusion of GA significantly enhanced the antibacterial activity, particularly in TAC-loaded hydrogels, which achieved the largest inhibition zones. The study highlights the synergistic effect of CNC and GA in stabilizing hydrogel structures and improving drug release profiles, offering a promising approach for advanced antimicrobial applications in biomedical materials.